Evaluation of CYP17A1 and CYP1B1 polymorphisms in male breast cancer risk. Issue 8 (August 2019) - Rizzolo, Piera; Silvestri, Valentina; Valentini, Virginia; Zelli, Veronica; Bucalo, Agostino; Zanna, Ines; Bianchi, Simonetta; Tibiletti, Maria Grazia; Russo, Antonio; Varesco, Liliana; Tedaldi, Gianluca; Bonanni, Bernardo; et al.
Abstract : Breast cancer in men is a rare and still poorly characterized disease. Inherited mutations in BRCA1, BRCA2 and PALB2 genes, as well as common polymorphisms, play a role in male breast cancer genetic predisposition. Male breast cancer is considered a hormone-dependent tumor specifically related to hyperestrogenism. Polymorphisms in genes involved in estrogen biosynthesis and metabolism pathways, such as CYP17A1 and CYP1B1, have been associated with breast cancer risk. Here, we aimed to investigate the role of CYP17A1 and CYP1B1 polymorphisms in male breast cancer risk. A series of 597 male breast cancer cases and 1022 male controls, recruited within the Italian Multicenter Study on male breast cancer, was genotyped for CYP17A1 rs743572, CYP1B1 rs1056836 and rs1800440 polymorphisms by allelic discrimination real-time PCR with TaqMan probes. Associations with male breast cancer risk were estimated using logistic regression. No statistically significant associations between male breast cancer risk and the three analyzed polymorphisms emerged. Similar results were obtained also when BRCA1 /2 mutational status was considered. No significant differences in the distribution of the genotypes according to estrogen receptor status emerged. In conclusion, our study, based on a large series of male breast cancer cases, is likely to exclude a relevant role of CYP17A1 and CYP1B1 polymorphisms in male breast cancer predisposition. Overall, these results add new data to the increasing evidence that polymorphisms in these genes may not be associated with breast cancer risk.